2015
DOI: 10.1097/sap.0b013e31829565d8
|View full text |Cite
|
Sign up to set email alerts
|

Limited Incision With Thorough Elevation Palatoplasty

Abstract: The LITE palatoplasty gives satisfactory results in elongating the soft palate and reconstructing a functional velar sling without leaving any raw surfaces that can be detrimental to healing and facial growth. And there was a better speech outcome without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…3). Compared to the results in our institute [12,13], patients with CP or SMCP who underwent palatoplasty showed unsatisfactory results, such as persistent hypernasality, which was also statistically significant (Table 3). Based on these results, it is assumed that the postoperative results of patients with KS are not satisfactory compared to patients who had similar degrees of severity in preoperative findings.…”
Section: Preoperative Evaluation and Determination Of Surgical Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…3). Compared to the results in our institute [12,13], patients with CP or SMCP who underwent palatoplasty showed unsatisfactory results, such as persistent hypernasality, which was also statistically significant (Table 3). Based on these results, it is assumed that the postoperative results of patients with KS are not satisfactory compared to patients who had similar degrees of severity in preoperative findings.…”
Section: Preoperative Evaluation and Determination Of Surgical Methodsmentioning
confidence: 72%
“…As per our modification, the extent of muscular dissection was greater than that described by Furlow, which released all abnormal insertions along the posterior border of the hard palate [12]. LITE is a modified two-flap palatoplasty that limits the incision at the anterior hard palate and elevates the movable palatal flap with thorough dissection over the entire palate [13]. DOZ or LITE was considered to be ineffective when the results of speech evaluation and nasopharyngoscopy showed that the palatal muscle was incompetent, and PPF was performed to create an anatomical barrier between the oral cavity and the nasal cavity to reduce nasal emission [15].…”
Section: Palatoplasty Methodsmentioning
confidence: 92%
See 1 more Smart Citation